2016
DOI: 10.1177/2051415816668943
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the diagnostic accuracy of ultrasound in the community and in the hospital setting for urinary calculi: A retrospective cohort study

Abstract: The objective of this article is to test whether there is a significant difference in diagnostic accuracy between hospital and community-based ultrasound (US) for the detection of urinary calculi in the United Kingdom (UK). Materials and methods: A 30-month, single-blind, retrospective cohort study of all patients referred to Kent and Canterbury Hospital urology multidisciplinary meeting for suspected urinary calculi was conducted. Only those investigated with US and non-contrast computed tomography (NCCT, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In fact, a recent study showed that the use of TC in the ER did not add any improvement to the diagnosis of OU, except in cases of great diagnostic uncertainty or in patients requiring immediate surgical intervention 22 . Similarly, the US assessment is associated with a 50% reduction in CT use in the ER 23 and it has been considered safe in the reevaluation of patients with appendicitis 24 or even those with unspecific abdominal complaints 25 , without the need for ionizing radiation.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, a recent study showed that the use of TC in the ER did not add any improvement to the diagnosis of OU, except in cases of great diagnostic uncertainty or in patients requiring immediate surgical intervention 22 . Similarly, the US assessment is associated with a 50% reduction in CT use in the ER 23 and it has been considered safe in the reevaluation of patients with appendicitis 24 or even those with unspecific abdominal complaints 25 , without the need for ionizing radiation.…”
Section: Discussionmentioning
confidence: 96%